An Assessment of Training Needs of Technical and Vocational Instructors (TVI’s) - Daisy T. Pedere (Alliance of Health Activists (AloHA), 2020)
Training has become a challenge for the Philippine education system. It has been agreed that both national growth and individual fulfillment are essential. This study was conducted among the Technical Instructors supervised institutions in Region VIII under the Commission on Higher Education. This study was conceived to define the required training methods, training style and training needs in crop production technology, animal production technology, post-harvest technology, management areas, and teaching related problems. Keywords: training needs; technical and vocational instructors